Impact of urbanization on agricultural ecological efficiency: evidence from China - Ximing Chen; Jie Shang; Xueqiang Ji (Ciência Rural, 2022)
ABSTRACT: Agricultural ecological efficiency is of great value to the government’s agricultural policy formulation. Research on the factors affecting agricultural ecological efficiency can provide support for the formation of countermeasures to improve agricultural ecological efficiency. Existing research has not conducted an in-depth analysis of the impact of urbanization on agricultural ecological efficiency, and there is a lack of relevant research on the impact of urbanization on agricultural ecological efficiency. This article is based on the data of 30 provinces and cities in China from 2009 to 2018, using the SBM model that considers undesired output, entropy method, Tobit model and other models and methods to measure agricultural ecological efficiency and urbanization comprehensive index, and analyze the impact of urbanization comprehensive index and urbanization indicators on agricultural ecological efficiency. The research results are as follows: 1) The overall agricultural ecological efficiency in China’s 30 provinces and cities has been increasing from 2009 to 2018. The eastern region has the highest agricultural ecological efficiency, followed by the western region, and the central and northeastern regions have relatively low values; 2) The comprehensive urbanization index of China’s 30 provinces and cities continued to grow from 2009 to 2018.The level of urbanization in the eastern region is the highest, in the central region has increased rapidly from 2009 to 2018, and in the western and northeastern regions is relatively low; 3) The overall increase in urbanization can promote the improvement of agricultural ecological efficiency. The impact of specific urbanization indicators on agricultural ecological efficiency is complex. Therefore, discussing the impact of urbanization on agricultural ecological efficiency cannot be considered from a single aspect, but should be analyzed from multiple perspectives.